Composting - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
It is increasingly important to step up and encourage the use of organic fertilizers in tropical agriculture because of the problems the use of chemical fertilizers presents to developing countries. For farmers in ACP countries chemical fertilizers...